Pola Interaksi Pemain Game Online Clash Of Clans (COC) Di Kalangan Mahasiswa Program Studi Pendidikan Sosiologi Dan Antropologi FKIP Universitas Lambung Mangkurat Banjarmasin - Kiptiyah, Mariyatul; Rochgiyanti, Rochgiyanti; Nasrullah, Nasrullah (Jurnal Tugas Akhir Mahasiswa Pendidikan Sosiologi, 2024)
This study aims (1) to explain the social processes carried out by online game Clash Of Clans (COC) players; (2) To describe the impact of playing the online game Clash Of Clans (COC). The method used in this research is qualitative method. The data sources were selected by purposive sampling. Data was collected by using observation, interview and documentation techniques. Technical data analysis uses qualitative analysis with data reduction steps, data presentation and conclusion drawing. The results of the study indicate that: (1) the social processes carried out by online game Clash Of Clans (COC) players consist of cooperation, competition and conflict; (2) The results of the discussion on the impact of playing the online game Clash Of Clans (COC) among students of the Sociology and Anthropology Education Study Program FKIP Lambung Mangkurat University Banjarmasin had an effect on waste, time, entertainment and psychology. Based on the results of the research, it is suggested that: (1) students should be able to take advantage of the facilities provided by the campus so that they can function properly; (2) The government can provide supervision over the use of the internet so that it can be used as best as possible.